Fabrication of curved diffractive optical elements by means of laser direct writing, electroplating, and injection compression molding. (November 2019) - Roeder, M.; Thiele, S.; Hera, D.; Pruss, C.; Guenther, T.; Osten, W.; Zimmermann, A.
Abstract: In this work, a new process chain for the fabrication of curved micro-structured optical elements by injection compression molding is investigated. The fabrication is demonstrated for the example of a curved diffractive optical element (DOE). In a first process step a master substrate is fabricated using laser direct writing on a curved glass substrate. Blazed diffractive micro-structures with lateral feature sizes down to 5 μm and height of 1.6 μm are created. A subsequent electroplating process is applied to create a nickel stamper to be used as a tool insert for the molding process. During electroplating, a 3 mm nickel layer is formed, transferring the diffractive structures from the master substrate into a solid mold insert. The nickel stamper shows an accurate reproduction of the micro-structures. The mold insert is integrated into an injection compression molding tool to replicate the optical elements. Results show that the blazed diffractive structures are replicated with a high quality. Tests of the components within a chromatic-confocal measurement setup confirm that they can potentially replace expensive conventional elements.